The role of the thymus in allogeneic hematopoietic stem cell transplantation. - Krenger, W; Holländer, G (2010)
Allogeneic haematopoietic stem cell transplantation (HSCT) is used to treat an increasing number of congenital and acquired disorders of the haematopoietic system. Even though cytoreductive conditioning regimens vary in intensity, all clinically used protocols invariably cause side effects that compromise transiently or long-term the response of the natural and the adaptive immune systems. However, in the context of the reconstruction of immunity, the generation of naïve T cells constitutes a slow process, and requires a functionally competent thymus. Unfortunately, regular thymic function is frequently suppressed by transplant-related toxicities. Most notably, graft-versus-host disease (GVHD) causes a state of posttransplantation immune deficiency. Here we discuss preclinical allogeneic HSCT models and clinical observations that have contributed to a detailed understanding of the cellular and molecular mechanisms responsible for the thymic dysfunction caused by acute GVHD. An in-depth knowledge of the mechanisms that control regular thymopoiesis and, conversely, affect thymus function is expected to provide the factual basis for the design of innovative therapies to recover T-cell numbers and function following allogeneic HSCT.